Interface of Two-component Bose-Einstein Condensates in Double-parabola Approximation - Thu, Nguyen Van (VNU Journal of Science: Mathematics - Physics, 2023)
In this work we proposed a simple method to determine the coordinate of interface of two-component Bose-Einstein condensates (BECs) in double parabola approximation (DPA). Based on this idea, the static properties of BECs have been investigated totally in DPA